Evaluation of large‐scale clinical trials on cardiovascular disease risk in patients with type 2 diabetes mellitus treated with dipeptidyl peptidase 4 inhibitors and a new class of drugs. Issue 5 (30th March 2017) - Kurose, Takeshi; Hamamoto, Yoshiyuki; Seino, Yutaka
Abstract : Several recent prospective cardiovascular clinical trials completed with newly developed drugs for the treatment of type 2 diabetes mellitus have been published. Caution must be used when interpreting these studies.